Exploring In-Service Teachers’ Views on Artificial Intelligence at the Secondary Level - Sinaga, Irene Riskiana Vionauli; Wisma Yunita (Universitas Cokroaminoto Palopo, 2025)
Artificial Intelligence (AI) is a new breakthrough in the educational paradigm in the 21st century learning era. This study examines the perception of in-service teachers towards the use of AI in the form of Chat GPT in the learning process at the private secondary school level and how its integration implications are for the curriculum applied. Participants in this study are in-service teachers at a private school at the secondary school level with a total of 16 teachers. This study uses a descriptive-qualitative design with questionnaire instruments based on Chan and Hu (2023) in Thararattanasuwan and Prachagool (2024) and interviews tailored to research needs. The data was analyzed using a Likert scale guide and simple statistical calculations. The results of the study show a positive perception of in-service teachers towards the use of AI, namely chat GPT which has good implications in the integration of the curriculum in the learning process in each subject by paying attention to its limitations. Therefore, it can be concluded that in-service teachers at the private secondary school level have a positive view of chat GPT and have been integrated in learning in accordance with the implementation of the curriculum.